L’EAU DANS LE COMMENTAIRE ANONYME SUR FRONTIN. - Peyras, Jean (Riparia, 2016)
<!–[if gte mso 9]> 72 1024x768 <![endif]–>This paper about the anonymous Commentum (VIth century ?) of Frontinus’s books (De agrorum qualitate and De controuersiis) brings to an end the studies that we carried out about the conception of the riparia by the Roman surveyors. This book gives interpretations inspired from Hygin, Siculus Flaccus and Agennius Urbicus, but also some original informations : rivers were used to demarcate each victorious owner’s soils (ager arcifinalis or ager occupatorius), marshes are not subseciua not surveyed, which are at the ends of the assigned lands of limitatio ; forests surrounded Tiber are not exploited because this river is sacred. <!–[if gte mso 9]> Normal 0 21 false false false <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabla normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –>